Identification of common salivary miRNA in oral lichen planus and oral squamous cell carcinoma: systematic review and meta-analysis - Maryam Koopaie; Parisa Akhbari; Mahnaz Fatahzadeh; Sajad Kolahdooz (BMC, 2024)
Abstract Background Oral lichen planus (OLP) is a chronic inflammatory condition that can impact patients' quality of life. While its exact etiology remains unclear, it is associated with an increased risk of malignant transformation. Currently, the diagnosis of OLP relies on clinical examination and histopathological analysis, which can be invasive. Therefore, there is an urgent need for non-invasive and accurate diagnostic biomarkers. This systematic review and meta-analysis aims to investigate the potential of salivary microRNAs as promising candidates for OLP diagnosis. This meta-analysis seeks to identify specific microRNAs that are differentially expressed and could serve as reliable biomarkers for OLP diagnosis. Methods Our strategy involved searching for pertinent keywords in multiple academic databases including Cochrane Library, Embase, LIVIVO, MEDLINE, Ovid, ProQuest, Scopus, Web of Science, Espacenet, and Google Scholar search engine. Upon identification, articles were screened and data extracted from the eligible studies. Split component synthesis method was utilized to assess specificity, sensitivity, likelihood and diagnostic odds ratios. The random-effects meta-analysis approach was used to combine study findings and develop pooled diagnostic performance metrics. Hierarchical summary receiver operating characteristic (ROC) plots were generated to determine area under the curve. Subgroup analyses concerning the type of saliva and control groups were also performed. Results Among the fourteen studies included in our systematic review, five were eligible for meta-analysis. Salivary microRNAs showed the pooled sensitivity of 0.80 (95% Confidence Interval (95% CI): 0.68-0.88), specificity of 0.89 (95% CI: 0.82-0.94), diagnostic odds ratio of 28.45 (95% CI: 10.40-77.80), and area under the curve (AUC) of 0.93 for OLP diagnosis. Unstimulated saliva had higher sensitivity and specificity than oral swirl samples as the biomarker medium for OLP diagnosis. Meta-analysis uncovered that miR-27a, miR-137, miR-1290, miR-27b, miR-4484, miR-142, and miR-1246 had the highest diagnostic odds ratio for OLP. Conclusions Our systematic review and meta-analysis demonstrate that salivary microRNAs can serve as valuable biomarkers for the diagnosis of OLP. The findings highlight the exceptional accuracy of salivary microRNAs in differentiating OLP patients from healthy controls and assessing the risk of malignant transformation.